Identification of maize inbreds for hybridization using agro-morphological traits and SSR markers through clustering and population structure analysis - Sneha S; SathyaSheela K.R.V; Ravikesavan R; Selvakumar T; BabuRajendraPrasad V; Sivakumar S; KumariVinothana N; Deepika V (Molecular Biology Reports, 2026)

Quantitative assessment of sugarcane yellow leaf disease impact on growth, yield, and juice quality in major Indian cultivars - R. Viswanathan; R. Selvakumar; K. Nithya; R. Arun Kumar; Shweta Singh; Chandramani Raj; D. Neelamathi; T. Lakshmipathy; R. Nithyanantham; K. Manivannan; K. Kaverinathan (Physiological and Molecular Plant Pathology, 2026)

Controlled condition screening assay to simulate wilt in sugarcane using soil and crop debris inocula - R. Viswanathan; C. G. Balaji; R. Selvakumar; P. Malathi; A. Ramesh Sundar; R. Nithyanantham; K. Manivannan (Indian Phytopathology, 2026)

Molecular Mapping and Diversity of Fusarium Isolates Associated with Wilt and Pokkah Boeng of Sugarcane in Tropical India - R. Viswanathan; R. Selvakumar; Chandramani Raj; R. Gopi; P. Malathi; A. Ramesh Sundar; A. Annadurai; S. Balasaravanan; R. Nithyanantham; K. Kaverinathan; K. Manivannan (Sugar Tech, 2026)

Retraction notice to “A review on network pharmacology based phytotherapy in treating diabetes- An environmental perspective” [Environ. Res. 202 (2021) 111656] - Meenakshi R. Venkateswaran; Tamil Elakkiya Vadivel; Sasidharan Jayabal; Selvakumar Murugesan; Subbiah Rajasekaran; Sureshkumar Periyasamy (Environmental Research, 2025)

Bioleaching assisted electrochemical reclamation of titanium from redmud using extremophilic Bacillus subtilis N3 - Punniyadharshini S; Unnamalai S; Sruthi K; Alagarsamy G; Manjima Sanil; Sankarganesh Jeyaraj; Prasana Manikanda Kartik J; Chandraraj K; Vinod Kumar Verma; Krishna Kumari V; Selvakumar R (Bioresource Technology Reports, 2025)

Temporal Dynamics and Characterization of Sugarcane Parental Pool for Rust Resistance under Tropical Climate - R Selvakumar; T Lakshmi Pathy; Gopalareddy Krishnappa; A Anna Durai; R Viswanathan (Tropical Plant Biology, 2025)

Radiological risk assessment of radon in groundwater of a tropical River Basin, SW India: integrating deterministic and probabilistic approaches - G. R. Anurani; S. Sukanya; Sabu Joseph; S. Selvakumar (Environmental Geochemistry and Health, 2025)

Widespread Occurrence of Colletotrichum falcatum Pathotype CF13 in the Subtropical India Dictates Continuous Pathogenic Virulence and Severe Sugarcane Crop Destructions - R. Viswanathan; Sujeet Pratap Singh; R. Selvakumar; Chandramani Raj; Dinesh Singh; Y. P. Bharti; M. L. Chhabra; Anuradha Sharma; Md. Minnatullah; Rakesh Mehra; Harvinder Singh Yadav; Sanjay Kumar Goswami; et al. (Sugar Tech, 2025)

Impact of Wilt on Flowering and Ratoon Establishment in Parental Clones of Sugarcane - R. Viswanathan; R. Selvakumar; P. Malathi; A. Ramesh Sundar; A. Anna Durai; R. Nithyanantham; K. Manivannan (Sugar Tech, 2025)

Effect of Carbon Nanomaterials on Soil and Plant Microbiome - Kasthuri Selvakumar; Kalaiselvi Thangavel; Senthamilselvi Dhandapani; Rajkishore S. K.; Bharani A.; Subhashini R. (Journal of Soil Science and Plant Nutrition, 2025)

Effectiveness of Mycorrhiza on Soil Enzyme Activity, Nutrient Content and Fruit Quality of Dragon Fruit in Acidic Soil Conditions - Ankita Sahu; Kundan Kishore; Upendra Kumar; G. Selvakumar; S. C. Sahoo; S. N. Dash; R. K. Nayak (Applied Fruit Science, 2025)

Textural characteristics of channel bed sediments and heavy minerals of the Cauvery River, Southern India: implications on depositional environments, provenance, tectonics and climate - M. Ramkumar; AL Fathima; G. Sugavanam; B. Velliyangiri; M. Selvakumar; S. Anbarasan; M. Sowmiya; S. Kiruthika; K. Balasubramani; V. Thirukumaran; P. D. Roy; R. Nagarajan; et al. (Journal of Sedimentary Environments, 2025)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Quinoline-quinoline schiff-base as an effective chromogenic, fluorogenic, and smartphone assisted RGB detection of Pb2+ ion in near aqueous medium - Kathirvel R; Poongodi M; Vetriarasu V; Vivekanandan K.E; Selvakumar K; Sami Al Obaid; Arivalagan Pugazhendhi; Geetha Venkatesan (Environmental Research, 2024)

Development of superhydrophobic/superoleophilic cotton micro dust waste functionalized SiO2 nanocomposite as an efficient adsorbent for oil/water separation - A. Dhakshana; R. Selvakumar; K. Vivekanand; M. Alagappan; K. Chandraraj; S. P. Suriyaraj (Nanotechnology for Environmental Engineering, 2024)

Impact of effluent parameters and vancomycin concentration on vancomycin resistant Escherichia coli and its host specific bacteriophage lytic activity in hospital effluent - P Nithiya; G Alagarsamy; P.B Sathish; D Rajarathnam; Xu Li; Sankarganesh Jeyaraj; Manjima Satheesh; R Selvakumar (Environmental Research, 2024)

First Report of Exserohilum rostratum Causing Sugarcane Leaf Spot in India - R. Selvakumar; M. Remya; R. B. Akshay Ravi; R. Viswanathan (Sugar Tech, 2023)

Revealing Adaptability of Sugar Beet (Beta vulgaris) Genotypes Through Environmental Interaction (GEI) connecting Variations in Tuber Yield - M. Shanmuganathan; D. Kumaresan; S. Geetha; M. Dhasarathan; M. Jayaramachandran; R. Sudhagar; T. Selvakumar; L. Chitra; S. Mohan; A. Gurusamy; K. Iyanar (Agricultural Research, 2023)

Recent advances in micropollutant removal and mitigation from water using three dimensional adsorbent materials - R. Selvakumar; A. Guhananthan; Thavamani Palanisami (Current Opinion in Environmental Science & Health, 2023)

Twisted top disease a destructive disease of sugarcane in India - R. Viswanathan; N. Geetha; K. P. Salin; R. Selvakumar; P. Malathi; A. R. Sundar; R. Nithyanantham; K. Manivannan (Indian Phytopathology, 2023)

Heterostructures of polyaniline and Ce–ZnO nanomaterial coated flexible PET thin films for LPG gas sensing at standard environment - D. Selvakumar; K.P. Sonu; G. Ramadoss; R. Sivaramakrishnan; R. Jayavel; M. Eswaramoorthy; K. Venkateswara Rao; A. Pugazhendhi (Chemosphere, 2023)

Effect of gamma-ray irradiated reduced graphene oxide (rGO) on environmental health: An in-vitro and in-vivo studies - S. Sivaselvam; A. Mohankumar; R. Narmadha; R. Selvakumar; P. Sundararaj; C. Viswanathan; N. Ponpandian (Environmental Pollution, 2023)

Genetic diversity in Groundnut (Arachis hypogaea. L) genotypes varying in maturity duration - R. Sangeetha Vishnuprabha; PL. Viswanathan; S. Manonmani; L. Rajendran; T. Selvakumar (Vegetos, 2022)

Varietal Break Down to Red Rot in the Sugarcane Variety Co 0238 Mimics Vertifolia Effect: Characterizing New Colletotrichum falcatum Pathotype CF13 - R. Viswanathan; Sujeet Pratap Singh; R. Selvakumar; Dinesh Singh; Y. P. Bharti; M. L. Chhabra; B. Parameswari; Anuradha Sharma; Md. Minnatullah (Sugar Tech, 2022)

Inheritance of purple colour and its different flavonoids profiling in F2 populations of tropical carrot (Daucus carota L.) - Raman Selvakumar; Pritam Kalia; Dalasanuru Chandregowda Manjunathagowda; R. S. Raje (Genetic Resources and Crop Evolution, 2022)

Revealing Gene Action of Different Root Pigments in Tropical Carrot (Daucus carota) - Raman Selvakumar; Pritam Kalia; R. S. Raje; Abhijit Kar (Agricultural Research, 2022)

Modified Scale for Evaluating Sugarcane Clones for Fusarium wilt Resistance with Plug Method of Inoculation - R. Viswanathan; R. Selvakumar; P. Malathi; A. R. Sundar (Sugar Tech, 2022)

Epidemiology of sugarcane wilt: predisposition by root borer Polyocha depresella a myth or reality - R. Viswanathan; R. Selvakumar; N. Geetha; C. G. Balaji; A. Annadurai; Adhini S. Pazhani; P. Malathi; A. Ramesh Sundar; R. Nithiyanantham; K. Manivannan (Indian Phytopathology, 2022)

Controlled Condition Testing (CCT): An Ideal High-Throughput Method for Screening of Pre-Release Clones and Progenies for Red Rot Resistance in Sugarcane - R. Viswanathan; R. Selvakumar; P. Malathi; N. Prakasam (Sugar Tech, 2021)

Graphene-based materials for environmental applications: a review - V. Karthik; P. Selvakumar; P. Senthil Kumar; Dai-Viet N. Vo; M. Gokulakrishnan; P. Keerthana; V. Tamil Elakkiya; R. Rajeswari (Environmental Chemistry Letters, 2021)

A low cost method for early detection of airborne Puccinia rust spores using glass slides and foldscope in the sugarcane field - R. Selvakumar; R. Viswanathan (Indian Phytopathology, 2021)

Identification of polyphenolic contents, in vitro evaluation of antioxidant and antidiabetic potentials of a polyherbal formulation-Mehani - Meenakshi R. Venkateswaran; Sasidharan Jayabal; Selvakumar Murugesan; Sureshkumar Periyasamy (Natural Product Research, 2021)

Trends in Biological Nutrient Removal for the Treatment of Low Strength Organic Wastewaters - J Rajesh Banu; J Merrylin; S Kavitha; R Yukesh Kannah; P Selvakumar; S Gopikumar; P Sivashanmugam; Khac-Uan Do; Gopalakrishnan Kumar (Current Pollution Reports, 2021)

Varietal Breakdown to Red Rot in Sugarcane Revealed by Comparing Two Colletotrichum falcatum Inoculation Methods - R. Viswanathan; R. Selvakumar (Sugar Tech, 2020)

Correction to: Escin, a Novel Triterpene, Mitigates Chronic MPTP/P-Induced Dopaminergic Toxicity by Attenuating Mitochondrial Dysfunction, Oxidative Stress, and Apoptosis - Govindasamy Pushpavathi Selvakumar; Thamilarasan Manivasagam; Karamkolly R. Rekha; Richard L. Jayaraj; Namasivayam Elangovan (Journal of Molecular Neuroscience, 2020)

Behaviour of Soil Borne Inoculum of Colletotrichum falcatum in Causing Red Rot in Sugarcane Varieties with Varying Disease Resistance - R. Viswanathan; R. Selvakumar; K. Manivannan; R. Nithyanantham; K. Kaverinathan (Sugar Tech, 2020)

Emergence of New Pathogenic Variants in Colletotrichum falcatum, Stalk Infecting Ascomycete in Sugarcane: Role of Host Varieties - R. Viswanathan; P. Padmanaban; R. Selvakumar (Sugar Tech, 2020)

Influence of land use changes on spatial erosion pattern, a time series analysis using RUSLE and GIS: the cases of Ambuliyar sub-basin, India - N. Nasir; R. Selvakumar (Acta Geophysica, 2018)

Validating a High Performance Liquid Chromatography-Ion Chromatography (HPLC-IC) Method with Conductivity Detection After Chemical Suppression for Water Fluoride Estimation - Joseph Dian Bondu; R. Selvakumar; Jude Joseph Fleming (Indian Journal of Clinical Biochemistry, 2018)

Epidemiology of Fusarium Diseases in Sugarcane: A New Discovery of Same Fusarium sacchari Causing Two Distinct Diseases, Wilt and Pokkah Boeng - R. Viswanathan; C. G. Balaji; R. Selvakumar; P. Malathi; A. Ramesh Sundar; C. Naveen Prasanth; M. L. Chhabra; B. Parameswari (Sugar Tech, 2017)

Effects of Fluoride on Bone in an Animal Model of Vitamin D Deficiency - Joseph Dian Bondu; M. S. Seshadri; R. Selvakumar; Jude Joseph Fleming (Indian Journal of Clinical Biochemistry, 2017)

Diversity of the cultivable gut bacterial communities associated with the fruit flies Bactrocera dorsalis and Bactrocera cucurbitae (Diptera: Tephritidae) - Nagalakshmi R. Gujjar; Selvakumar Govindan; Abraham Verghese; Sudhagar Subramaniam; Ravi More (Phytoparasitica, 2017)

Opportunity to restore irrigation tanks in the Cauvery delta by mining and deepening - T. R. Neelakantan; C. R. Suribabu; R. Selvakumar (Environment, Development and Sustainability, 2017)

Silk–PVA Hybrid Nanofibrous Scaffolds for Enhanced Primary Human Meniscal Cell Proliferation - Mamatha M. Pillai; J. Gopinathan; B. Indumathi; Y. R. Manjoosha; K. Santosh Sahanand; B. K. Dinakar Rai; R. Selvakumar; Amitava Bhattacharyya (The Journal of Membrane Biology, 2016)

Differential expression analysis of a select list of genes in susceptible and resistant heirloom tomatoes with respect to Pseudomonas syringae pv. tomato - Selvakumar Veluchamy; Dilip R. Panthee (European Journal of Plant Pathology, 2015)

Escin, a Novel Triterpene, Mitigates Chronic MPTP/p-Induced Dopaminergic Toxicity by Attenuating Mitochondrial Dysfunction, Oxidative Stress, and Apoptosis - Govindasamy Pushpavathi Selvakumar; Thamilarasan Manivasagam; Karamkolly R. Rekha; Richard L. Jayaraj; Namasivayam Elangovan (Journal of Molecular Neuroscience, 2015)

Effect of Biotin and Galactose Functionalized Gelatin Nanofiber Membrane on HEp-2 Cell Attachment and Cytotoxicity - R. Selvakumar; S. Nazar Mohamed Mohaideen; S. Aravindh; C. Sabarinath; M. Ananthasubramanian (The Journal of Membrane Biology, 2014)

Revealing effect of bathymetry over tsunami run-up through factor analysis - R. Selvakumar; S. M. Ramasamy (Arabian Journal of Geosciences, 2013)

Geraniol Ameliorates the Motor Behavior and Neurotrophic Factors Inadequacy in MPTP-Induced Mice Model of Parkinson’s Disease - Karamkolly R. Rekha; Govindasamy P. Selvakumar; Subramaniam Sethupathy; Karunanidhi Santha; Ramu Inmozhi Sivakamasundari (Journal of Molecular Neuroscience, 2013)

Anomalous Activity Measurements of Creatine (Phospho) Kinase, CK-MB Isoenzyme in Indian Patients in the Diagnosis of Acute Coronary Syndrome - Jude Joseph Fleming; Harish P. Janardhan; Arun Jose; R. Selvakumar (Indian Journal of Clinical Biochemistry, 2011)

Good Laboratory Practices - R. Selvakumar (Indian Journal of Clinical Biochemistry, 2010)

Usefulness of ferroxidase activity of ceruloplasmin in the diagnosis of Wilson’s disease - J. J. Fleming; S. Santhosh; R. Selvakumar; A. Jose; C. E. Eapen (Indian Journal of Clinical Biochemistry, 2009)

External quality assurance—Role of ACBI/CMC scheme - F. S. Geethanjalai; J. Fleming; S. Swaminathan; R. Selvakumar (Indian Journal of Clinical Biochemistry, 2006)

Report of a trial with lyophilised QC sera in the CMCH/ACBI EQAS programmes in India - R. Selvakumar; S. Swaminathan; J. J. Fleming (Indian Journal of Clinical Biochemistry, 2004)

In vitro propagation of the medicinal plant Plumbago zeylanica L. Through nodal explants - V. Selvakumar; P. R. Anbudurai; T. Balakumar (In Vitro Cellular & Developmental Biology - Plant, 2001)

Thyroid autoantibody measurement by enzyme immunoassay - D. Charles Stephen; Nihal Thomas; R. Selvakumar; M. S. Seshadri; A. S. Kanagasabapathy (Indian Journal of Clinical Biochemistry, 1997)

Prevalence of neutralising antibodies to Berne virus in animals and humans in Vellore, South India - D. W. G. Brown; R. Selvakumar; D. J. Daniel; V. I. Mathan (Archives of Virology, 1988)